Facile Room Temperature Deposition of ZnS Thin Films on Flexible Plastic Substrates via Nebulized Spray Method - Paul, A.; John, J. C .; Jose, J.; Ambily, V. J.; Joseph, N.; Augustine, S.; Thomas, S.; Sebastian, T. (Journal of Scientific Research, 2024)
This study focuses on investigating a potential method for depositing zinc sulfide (ZnS), in thin film form at room temperature. A facile and effective approach was employed in this study, wherein a suspension of ZnS powder in methanol was applied onto flexible plastic substrates using a spray deposition method. Structural analysis of the resulting films revealed a broad X-ray diffraction peak along the (100) plane, indicating the presence of nanoscale crystallites. The band gap of the ZnS films was determined to be 3.78 eV. Furthermore, the films exhibited photo luminescence emission centered at a wavelength of 410 nm, which corresponds to the blue edge of the chromaticity diagram.